Analisis Respon Muzakki Terhadap Rencana Pembentukan Unit Pengumpul Zakat - Idel Waldelmi (Jurnal Ekonomi Sakti, 2018)
This research is in background, zakat that can encourage capital investment and cooperation in industry and commerce where the pushing factor is psychological motive and economic motive and the purpose of this research to know and analyze the muzakki response to UPZ formation in University of Lancang Kuning and what can be done By UPZ managers in collecting zakat. Data analysis method used in this research is descriptive analysis method. The results of to muzakki response to zakat collection unit (UPZ) with score score score 4.08 in high category. Of the seven items in question there are three items that are still in the category below average ie the clarity of the office pelayann zakat, uni way in collecting zakat and zakat collection system work. The obstacles faced by managers and officers in carrying out the mandate entrusted to the officers of the UPZ limited ability, lack of experience and time socialize and officers who time is limited.